Visible, invisible: Black women in higher education - Showunmi, Victoria (Frontiers in Sociology, 2023)
Word count: 162 words This paper explores race and gender in the context of higher education, analysing the experiences of Black women in academia to create a better understanding of what it is to be Black and a woman in contemporary British society. The main themes of this paper are elaborated through the lens of critical Black feminism. The historical origins of inequalities are outlined foregrounding their influence on how Black women are described and regarded. The damaging impact of everyday and sophisticated racism intersecting with sexism is explored and exemplified. Concepts and theories serve to elucidate the discrimination suffered by Black women in academic roles. White women do not offer unequivocal support to their Black colleagues and may even undermine their career progression. When Black women gain leadership roles, the traditional characteristics associated with leaders often conflict with the stereotypical expectations of Black women. A closer examination of higher education reveals the extent of the racial trauma endured by Black women and the resultant decline in their well-being.